PROBLEM-BASED LEARNING: 21ST CENTURY VOCATIONAL EDUCATION - RINA NOVALINDA; M GIATMAN; SYAHRIL; AMBIYAR; MELDA FAJRA (CV KULTURA DIGITAL MEDIA, 2020)
The development of creativity in the 21st century is a skill that requires students to master perseverance and problem solving combined with good teamwork. Creativity in the skill component of the 21st century is a much-needed new demand. Along with the rapid development of the era, education's role becomes essential in preparing students, especially vocational schools that emphasize the mastery of science, skills, attitudes, and values needed by the industrial world, to have 21st-century skills. This is done by changing teachers' roles from information providers and communicators to facilitators to share information and knowledge and train learners' problem-solving skills. Constructivism learning is one alternative to practising 21st-century skills. Meaningful problem-based learning is applied primarily to help thinking skills, problem-solving, and intellectual skills and learning to be an independent and creative learner.